Archaeology, heritage, and civic engagement : working toward the public good - Little, Barbara J.; Shackel, Paul A. (Walnut Creek, California : Left Coast Press, 2014)
"The definition of "public archaeology" has expanded in recent years to include archaeologists' collaborations with and within communities and activities in support of education, civic renewal, peacebuilding, and social justice. Barbara Little and Paul Shackel, long-term leaders in the growth of a civically-engaged, relevant archaeology, outline a future trajectory for the field in this concise, thoughtful volume. Drawing from the archaeological study of race and labor, among other examples, the authors explore this crucial opportunity and responsibility, then point the way for the discipline to contribute to the contemporary public good"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Community archaeology; Archaeology -- Social aspects; Cultural property -- Social aspects; Common good; Electronic books